Dynamic Simulation of Fixed‐Bed Chemical‐Looping Combustion Reactors Integrated in Combined Cycle Power Plants. Issue 10 (7th July 2016) - Chen, Chen; Han, Lu; Bollas, George M.
Abstract: Chemical‐looping combustion (CLC) is a promising and efficient method for power generation with in situ CO2 capture. In this work, we focus on high‐pressure fixed‐bed CLC reactors integrated with combined cycle (CC) power plants. Specifically, the dynamic nature of fixed‐bed chemical‐looping reactors and the many kinetically controlled reactions necessitate the use of dynamic modeling to evaluate power plant performance, efficiency, stability, and feasibility under transient operation. We present a dynamic model for an integrated CLC–CC power plant and transient analyses of the integrated plant performance. A network of dynamically operated fixed‐bed reactors fed with natural gas comprises the CLC plant component. A dynamic model is developed and tuned to match the performance of a commercial combined cycle power plant. The transient variations of the integrated plant in terms of power, temperature, and pressure profiles are presented. The simulation results show that despite the inherent batch‐type operation of the CLC reactor, the operation of the combined cycle is relatively unaffected, and there are small oscillations of approximately 2 % around the desired steady‐state conditions. Abstract : Model integration : A dynamic model of chemical‐looping combustion (CLC) reactors integrated in a combined cycle power plant is developed and applied for transient system analysis. A network of dynamically operated fixed‐bed reactors fed with natural gas comprises the CLC plant component. The plant has a good thermal efficiency and satisfies stability requirements.